Desmids of some selected areas of Bangladesh. 3. Docidium, Pleurotaenium, Triplastrum and Triploceras - Islam, AKM Nurul; Akter, Nasima (Bangladesh Journal of Plant Taxonomy, 2005)
23 taxa belonging to Pleurotaenium, 2 under Triploceras and 1 each under Docidium and Triplastrum have been recorded in this paper from some selected areas of Bangladesh. Of these, 11 are new records for the country. Keywords: Desmids, Docidium, Pleurotaenium, Triplastrum, Triploceras, Bangladesh DOI: 10.3329/bjpt.v12i1.608 Bangladesh J. Plant Taxon. 12(1): 11-23, 2005 (June)